Regulation of CEACAM Family Members by IBD-Associated Triggers in Intestinal Epithelial Cells, Their Correlation to Inflammation and Relevance to IBD Pathogenesis - Saiz-Gonzalo, Gonzalo; Hanrahan, Naomi; Rossini, Valerio; Singh, Raminder; Ahern, Mary; Kelleher, Maebh; Hill, Shane; O’Sullivan, Ruairi; Fanning, Aine; Walsh, Patrick T.; Hussey, Seamus; Shanahan, Fergus; et al. (Frontiers in Immunology, 2021)
Carcinoembryogenic antigen cellular adhesion molecules (CEACAMs) are intercellular adhesion molecules highly expressed in intestinal epithelial cells. CEACAM1,-3,-5,-6,-7 are altered in patients suffering from colon cancer and inflammatory bowel diseases (IBD) but their role in the onset and pathogenesis of IBD is not well known. Herein, we aim to correlate CEACAM1,-3,-5,-6,-7 expression to the degree of inflammation in pediatric and adult IBD colon biopsies and to examine the regulation of CEACAMs on human intestinal epithelial cell lines (C2BBe1/HT29) by different IBD-associated triggers (cytokines, bacteria/metabolites, emulsifiers) and drugs (Azathioprine, Prednisolone, Tofacitinib). Biopsies from patients with pediatric Crohn’s disease (CD) and adult ulcerative colitis (UC, active/inactive disease) showed a significant increase in CEACAM3,-5,-6 expression, while CEACAM5 expression was reduced in adult CD patients (active/inactive disease). Intestinal epithelial cells cultured with a pro-inflammatory cytokine cocktail and Adherent-invasive Escherichia coli (AIEC) showed a rapid induction of CEACAM1,-5,-7 followed by a reduced expression overtime and a constant expression of CEACAM3, correlating with IL-8 expression. Cells cultured with the emulsifier polysorbate-80 resulted in a significant induction of CEACAM3,-5,-6,-7 at a late time point, while SCFA treatment reduced CEACAM1,-5,7 expression. No major alterations in expression of CEACAMs were noted on cells cultured with the commensal Escherichia coli K12 or the pathogen Salmonella typhimurium. IBD-drugs and particularly Tofacitinib significantly reduced cytokine-induced CEACAM1,-3,-5,-6,-7 expression associated with a reduced IL-8 secretion. In conclusion, we provide new evidence on the regulation of CEACAMs by different IBD-associated triggers identifying a role of CEACAMs in the onset and progression of IBD.